Xenogenesis‐Production of Channel Catfish × Blue Catfish Hybrid Progeny by Fertilization of Channel Catfish Eggs with Sperm from Triploid Channel Catfish Males with Transplanted Blue Catfish Germ Cells. (18th November 2016) - Perera, Dayan A.; Alsaqufi, Ahmed; Shang, Mei; Wade, Donny C.; Su, Baofeng; Elaswad, Ahmed; Fobes, Michael; Beam, Renee; Garcia, Gemerlyn; Dunn, David A.; Lipke, Elizabeth A.; Dunham, Rex A.
Abstract: Putative spermatogonia A from a fresh‐cell isolate or a density‐gradient‐centrifuged isolate from the testes of Blue Catfish Ictalurus furcatus were transplanted into the gonads of triploid Channel Catfish I. punctatus . The cells were introduced into gonads of the host via catheterization (2 × 10 4 –1.43 × 10 6 cells) or by surgically inserting the cells directly into the gonad (7 × 10 4 –1.25 × 10 5 cells). Ten months after implantation, DNA was analyzed from biopsies of the gonads and seven of eight males were found to be xenogenic, having Blue Catfish cells in their gonads. The xenogenic males successfully courted normal Channel Catfish that had been induced with hormones to ovulate, but none of the eggs hatched, indicating inadequate sperm production, an inability to ejaculate, and/or low sperm quality. Male xenogenic catfish treated with luteinizing hormone releasing hormone analog had well‐developed testes, and sperm production was detected in three of seven xenogenic males examined 2 years after transplantation. Sperm were removed from a male that had been surgically transplanted with Blue Catfish cells and used to fertilize eggs from a hand‐stripped Channel Catfish female. One percent of these eggs hatched. All seven surviving 6‐month‐old progeny of this male had the external morphology, swim bladder shape, nuclear DNA profile, and mitochondrial DNA profile of female Channel Catfish × male Blue Catfish F1 hybrids, indicating that this triploid Channel Catfish male produced Blue Catfish sperm. This is the first report of successful production of xenogenic catfish and the first report of producing 100% hybrid progeny using xenogenesis in fish.